2018
DOI: 10.1177/0962280218810911
|View full text |Cite
|
Sign up to set email alerts
|

Predicting diabetes-related hospitalizations based on electronic health records

Abstract: Objective: To derive a predictive model to identify patients likely to be hospitalized during the following year due to complications attributed to Type II diabetes. Methods: A variety of supervised machine learning classification methods were tested and a new method that discovers hidden patient clusters in the positive class (hospitalized) was developed while, at the same time, sparse linear support vector machine classifiers were derived to separate positive samples from the negative ones (non-hospitalized)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Many models have been used to predict a patient admission to a hospital, mortality and other health care applications based on comorbidities. Some examples include: predicting morbidity of patients with chronic obstructive pulmonary disease [ 7 ], febrile neutropenia [ 8 ], as well as classifying the hospitalization of patients with preconditions on diabetes [ 9 ], heart disease [ 10 , 11 ], and hospital readmission for patients with mental or substance use disorders [ 12 ]. Recent advances in the machine learning literature have suggested that sparse classifiers, those that use few variables (e.g., 1-regularized Support Vector Machines), have stronger predictive power and generalize better on out-of-sample data points than very complex classifiers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many models have been used to predict a patient admission to a hospital, mortality and other health care applications based on comorbidities. Some examples include: predicting morbidity of patients with chronic obstructive pulmonary disease [ 7 ], febrile neutropenia [ 8 ], as well as classifying the hospitalization of patients with preconditions on diabetes [ 9 ], heart disease [ 10 , 11 ], and hospital readmission for patients with mental or substance use disorders [ 12 ]. Recent advances in the machine learning literature have suggested that sparse classifiers, those that use few variables (e.g., 1-regularized Support Vector Machines), have stronger predictive power and generalize better on out-of-sample data points than very complex classifiers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many models have been used to predict a patient admission to a hospital, mortality and other health care applications based on comorbidities. Some examples include: predicting morbidity of patients with chronic obstructive pulmonary disease [6], febrile neutropenia [7], as well as classifying the hospitalization of patients with preconditions on diabetes [8], heart disease [9,10], and hospital readmission for patients with mental or substance use disorders [11]. Recent advances in the machine learning literature have suggested that sparse classifiers, those that use few variables (e.g., l1-regularized Support Vector Machines), have stronger predictive power and generalize better on out-of-sample data points than very complex classifiers [12].…”
Section: Introductionmentioning
confidence: 99%
“…MLAs have been shown to improve precision in identifying individuals at risk of disease. (5)(6)(7)(8)(9)(10)…”
Section: Advantages Of MLmentioning
confidence: 99%